Efektivitas Pendidikan Karakter Melalui Metode Jurnal Refleksi Harian Siswa Kelas III A SDN 262 Panyileukan Kota Bandung - Elza Amalia Salsya Bani; Komariah Komariah (Journal on Education, 2023)
This study aims to describe the character of class III A students at SDN 262 Panyileukan that arise because of the awareness that is formed from the results of applying the daily reflective journal method at school. The daily reflection journal method is not limited to just one subject, but covers the entire teaching and learning process. This research uses a descriptive qualitative research type method. Data collection techniques are carried out through observation and documentation. The data obtained comes from primary data sources from teachers and students as well as secondary data sources from articles and documentation of these activities. Based on the data taken, it shows that there is a big influence on changes in the character of students at SDN 262 Panyileukan after applying the daily reflection journal method. Seeing the character problems and the many children who have unstable emotions, the teacher took the initiative to make different reflection activities, namely through a daily journal. This activity is carried out by students by writing down the positive and negative activities they have done while at school. Daily reflection journal activities as the application of character to students are carried out unconsciously and without coercion or rules from anyone. From this explanation it can be seen that the reflection method is effectively used.